Complete mitochondrial genome of Chironomus flaviplumus (Diptera: Chironomidae) collected in Korea - Kiyun Park; Won-Seok Kim; Jae-Won Park; Ihn-Sil Kwak (Mitochondrial DNA. Part B. Resources, 2021)
The complete mitochondrial genome of Chironomus flaviplumus was sequenced. The circular mitochondrial genome is 15,739 bp and consists of 13 protein-coding, two ribosomal RNAs, and 22 transfer RNA genes (GenBank accession no. MW770891). Results of phylogenetic analysis indicate that the species clustered with other species of the family Chironomidae. This study is helpful to the identification of C. flaviplumus larvae, which is difficult to be identified by morphology.